White root rot of Bletilla striata: the pathogen, biological characterization, and fungicide screening - Liang, Fang; Jiang, Xuejing; Liu, Lijuan; Wang, Feihu; Liu, Feng; Hu, Saixue; Tan, Lijun; Chen, Xiao; Xu, Yixuan; Xu, Xiulan; Jiang, Liqiong; Liu, Yinggao; et al. (Frontiers in Microbiology, 2024)
Bletilla striata is an endangered traditional medicinal herb in China. In May 2020, the emergence of white root rot severely impacted the quality and yield of B. striata, affecting about 5% of the plants at plant nurseries of the Chengdu Academy of Agricultural and Forestry Sciences. Through a series of experiments and evaluations, the pathogen was identified as Fusarium solani. This is the first report of B. striata white root rot caused by F. solani in Sichuan, China. To better understand this disease and provide data support for its control, a combination of morphological, molecular characterisation and pathogenicity determination was used in this study for assessment. Meanwhile, the effects of different carbon and nitrogen sources, culture medium, temperature, photoperiod and pH on mycelial growth and spore production of F. solani were investigated. In addition, effective fungicides were screened and the concentration ratios of fungicides were optimized using response surface methodology (RSM). The experimental results showed that sucrose was the optimum carbon source for the pathogen, and the optimum temperature and pH were 25°C and pH 7, respectively, while light did no significant effect. Effective fungicides were screened, among which difenoconazole showed the strongest inhibition with EC50 of 142.773 µg/mL. The optimum fungicide concentration scheme (difenoconazole, pyraclostrobin, and thiophanate-methyl at 395.42, 781.03, and 561.11 µg/mL, respectively) was obtained using response surface methodology (RSM) to improve the inhibition rate of 92.24 ± 0.34%. This study provides basic data for the pathogen characterization of B. striata white root rot and its potential fungicides in Sichuan, China. In addition, the optimal fungicide concentration ratios were obtained through response surface methodology (RSM) optimization, which significantly enhanced the fungicidal effect and provided a scientific basis for the future control of B. striata white root rot.